2022
DOI: 10.3390/antibiotics11070912
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Short-Term High Dose Pulsed Dapsone Combination Therapy in the Treatment of Chronic Lyme Disease/Post-Treatment Lyme Disease Syndrome (PTLDS) and Associated Co-Infections: A Report of Three Cases and Literature Review

Abstract: Lyme disease and associated co-infections are increasing worldwide and approximately 20% of individuals develop chronic Lyme disease (CLD)/Post-Treatment Lyme Disease Syndrome (PTLDS) despite early antibiotics. A seven- to eight-week protocol of double dose dapsone combination therapy (DDDCT) for CLD/PTLDS results in symptom remission in approximately 50% of patients for one year or longer, with published culture studies indicating higher doses of dapsone demonstrate efficacy against resistant biofilm forms of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 138 publications
(222 reference statements)
0
27
0
Order By: Relevance
“…The combinations of dapsone with rifampicin, clofazimine or both are already the therapies of choice to treat multidrug-resistant M.tuberculosis and leprosy have ample evidence for safety and tolerability in that population(46- 49). Furthermore, clinical studies have demonstrated efficacy of dapsone combination therapy in Lyme disease patients with chronic symptoms/PTLD(50)(51)(52). The results of this study and welldocumented use in humans make this combination attractive for further investigation.The presence of Bb DNA in tissues and xenodiagnostic tick midguts in the absence of Bb RNA occurred in mice in most combination therapy groups.…”
mentioning
confidence: 70%
“…The combinations of dapsone with rifampicin, clofazimine or both are already the therapies of choice to treat multidrug-resistant M.tuberculosis and leprosy have ample evidence for safety and tolerability in that population(46- 49). Furthermore, clinical studies have demonstrated efficacy of dapsone combination therapy in Lyme disease patients with chronic symptoms/PTLD(50)(51)(52). The results of this study and welldocumented use in humans make this combination attractive for further investigation.The presence of Bb DNA in tissues and xenodiagnostic tick midguts in the absence of Bb RNA occurred in mice in most combination therapy groups.…”
mentioning
confidence: 70%
“…In five separate clinical studies involving more than 365 patients, dapsone combination therapy led to statistically verified improvement in relieving eight major Lyme symptoms in our patients, including sweats/chills, fatigue, joint, muscle, and/or nerve pain, headaches, insomnia, and cognition [ 50 , 51 , 102 , 103 , 104 ]. In a 6th clinical case study involving chronic LD and Behçet’s disease (a severe multisystemic autoimmune illness), a patient who had been ill for 20 years reported significant symptom improvement when pyrazinamide (PZA) was added to dapsone combination therapy (DDSCT) despite a history of failing multiple disease-modifying antirheumatic drugs (DMARDS) [ 105 ].…”
Section: Introductionmentioning
confidence: 81%
“…Among 14 antibiotics and 25 antibiotic combinations for activity against stationary phase B. henselae in culture, methylene blue and rifampin were the most active agents against the biofilm B. henselae after 6 days of drug exposure, whereas both rifampin and methylene blue and azithromycin and methylene blue completely eradicated the biofilm form of B. henselae in culture after treatment for 6 days [ 101 ]. To date, only two studies have examined using rifampin, azithromycin, and methylene blue along with tetracycline, rifampin, and dapsone in the treatment of chronic Lyme, Babesia , and chronic bartonellosis, with variable results [ 102 , 103 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations